Anaemia and depletion of iron stores as risk factors for postpartum depression: a literature review - Andréanne Wassef; Quoc Dinh Nguyen; Martin St-André (Taylor & Francis Group, 2019)
Purpose: Iron-deficiency and anaemia are common in pregnant and postpartum women because of increasing iron demand and blood loss. Many women also enter pregnancy with pre-depleted iron stores. We reviewed the evidence linking anaemia and/or iron-deficiency to postpartum depression (PPD). Methods: We identified seventeen studies in four databases including randomized-controlled trials (RCTs) and observational studies assessing the impact of anaemia, iron-deficiency and iron supplementation on the risk of PPD. We extracted data on sample size, geographical region, obstetrical complications, measures of depression, haemoglobin, iron levels and intake of iron supplementation and critically appraised the results from the studies. Results: Eight out of ten studies found higher risk for PPD (r − 0.19 to −0.43 and ORs 1.70-4.64) in anaemic women. Low ferritin in the postpartum period but not during pregnancy was associated with increased risk of PPD. Iron supplementation in the postpartum period decreased risk of PPD in four out of five studies, whereas it did not protect from PPD if given during pregnancy. Limitations include study heterogeneity, discrepancy of prevalence of PPD and usage of a screening tool for evaluation of PPD. Conclusion: Anaemia and/or iron-deficiency may contribute to PPD in at-risk women. Further studies should elucidate the association between these entities.